Analisis Faktor-Faktor Penentu Kinerja Ekspor Industri Olahan Dilihat Dari Sisi Penawaran Di Bali - Apriana, Kadek Dody; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 3, Maret 2015 (pp. 139 - 219), 2015)
Export Bali consists of several commodities, and one of the prominent commodity groups is the industrial sector. Based on  bali export data can be seen that the development of industrial commodities are unstable . Every year there is a change which became a top ten commodities, such as in 2000, only four commodities which are the top ten, namely textiles, wooden handicrafts, silver and shell crafts. The purpose of this study was to determine the effect of a variable number of companies (X 1 ), the cost of labor (X 2 ), the value of the electricity used (X 3 ), premium (X 4 ), diesel fuel (X 5 ), oil (X 6 ), kerosene (X 7 ), coal (X 8 ), the cost of inputs (X 9 ), and indirect taxes (X 10 ), the affect of performance export processing industry in Bali terms of volume, value and market share. Based on the results of research on each model it is obtained that the number of companies , and the cost of inputs coined a positive effect on the alpha 1 % of the performance export processing industry in Bali, while the diesel fuel and indirect taxes have a negative effect on the alpha 5 % of the performance export processing industry in the period 2008-2012.
Keywords: export performance, industrial processing, tobit, panel data